Concurrence of elevated FeNO and airway hyperresponsiveness in nonasthmatic adolescents. Issue 3 (15th January 2020) - Kalm‐Stephens, Pia; Malinovschi, Andrei; Janson, Christer; Venge, Per; Nordvall, Lennart; Alving, Kjell
Abstract: Objectives: The aim of this study was to investigate airway responsiveness and eosinophil and neutrophil inflammatory markers in clinically confirmed nonasthmatic adolescents with elevated fractional exhaled nitric oxide (FeNO), a marker of type‐2 inflammation in the airways. Methodology: A total of 959 subjects from a general population, aged 12 to 15 years, answered a standardised questionnaire and underwent FeNO measurements at a screening visit at school. Adolescents without asthma, who had elevated FeNO (FeNO100  > 15 ppb) (n = 19), and control subjects, with low FeNO (FeNO100  < 5 ppb) and without reported symptoms of asthma or allergy (n = 28), participated in a follow‐up study where FeNO50, airway responsiveness to methacholine (PD20 ), blood eosinophil counts, and serum neutrophil lipocalin (HNL) and myeloperoxidase (MPO) levels were measured. Questionnaire follow‐ups were performed 4 and 16 years later. Results: Airway responsiveness (PD20 : 6.94 [1.87, 11.39] vs 11.42 [6.33, 59.4] µmol; P  < .05) and blood eosinophil counts (0.31 [0.20, 0.44] vs 0.13 [0.1, 0.22] 10 9 /L; P  < .001) (geometric mean [95% CI]) were higher among cases than controls. A significant correlation between blood eosinophils and FeNO was found (rho = 0.41; P  = .005). In contrast, serum HNL and MPO were lower in cases than controls ( P  < .05 both), and there was a negative correlation between HNL and FeNO ( r  = −0.31; P  = .04). At both follow‐ups, a higher proportion of subjects reported allergic symptoms compared with baseline ( P  = .02, P  = .01). Conclusions: Elevated FeNO in nonasthmatic adolescents was associated with airway hyperresponsiveness, elevated blood eosinophil counts, and lower systemic activation of neutrophils.